Adaptivity in mimetic difference schemes: one-dimensional transient problems. (January 2019) - Caldern, G; Carrillo E, J C; Villamizar, J; Torres, C; Castillo, J
Abstract: In this paper, we present an h -adaptive process that defines an optimal mesh to compute the solution transient of convection-diffusion-reaction boundary value problems by using mimetic numerical methods. The estimation of the error, in the spatial variable, is made from the discrete version of the gradient operator. The numerical experiment shows the good behavior of the procedure.